Assessing impacts of different land use scenarios on water budget of Fuhe River, China using SWAT model - Can, Tao; Xiaoling, Chen; Jianzhong, Lu; Gassman, Philip W.; Sabine, Sauvage; José-Miguel, Sanchez Perez (International Journal of Agricultural and Biological Engineering, 2015)
The Soil and Water Assessment Tool (SWAT) model was used to assess the impacts of different land use scenarios on hydrological processes in the Fuhe watershed in Poyang Lake Basin, East China. A total of 12 model parameters were calibrated with observed monthly runoff data for 1982-1988 and validated for 1991-1998 for baseline conditions. The baseline test results of R2 and Nash-Sutcliffe model efficiency (NSE) values ranged between 0.88 and 0.94 across the calibration and validation periods, indicating that SWAT accurately replicated the Fuhe watershed streamflow. Several different land use scenarios were then simulated with the model, focusing on the impacts of land use change on the hydrology of the watershed. The results of hypothetical scenario simulations revealed that surface runoff declined while groundwater recharge and evapotranspiration (ET) increased, as forest land, agriculture land and/or grassland areas increased, as well as when paddy field and urban areas decreased. These results further showed that forest land has a higher capacity to conserve the water as compared to pasture land. The results of the real scenario simulations revealed that urbanization is the strongest contributor to changes in surface runoff, water yield, and ET. Urbanization can be considered as a potential major environmental stressor controlling hydrological components.Keywords: SWAT model, land use, streamflow, water budget, scenario simulation, Poyang Lake, Fuhe watershedDOI: 10.3965/j.ijabe.20150803.1132 Online first on [2015-03-17]Citation: Tao C, Chen X L, Lu J Z, Gassman P W, Sabine S, José-Miguel S P. Assessing impacts of different land use scenarios on water budget of Fuhe River, China using SWAT model. Int J Agric & Biol Eng, 2015; 8(3): 95－109.